Factors Associated with Violent Behavior among Adolescents in Northeastern Brazil - Roberto Jerônimo dos Santos Silva; Nara Michelle Moura Soares; Antônio César Cabral de Oliveira (The Scientific World Journal)
The aim of this study was to identify prevalence and factors associated with violent behavior among adolescents in Aracaju and Metropolitan region. The study included 2207 adolescents (16.03 ± 1.08 years old) enrolled in high schools of the State Public Network. Violent behavior was identified from question 14 of the YRBS-2007 questionnaire with responses categorized as “never” and “one or more times.” Higher prevalence in males in relation to risk factors for adoption of violent behavior was found: cigarette consumption (7.3%), alcohol consumption (39.1%), and marijuana use (3.4%). Data analysis used descriptive statistics and logistic regression with hierarchical model at two levels: (a) sociodemographic variables and (b) behavioral variables. For both sexes, association between violent behavior and cigarette smoking (OR = 3.77, CI 95% = 2.06–6.92 and OR = 1.99, CI 95% = 1.04 to 3.81, male and female, resp.) and alcohol consumption (OR = 3.38, CI 95% = 2.22 to 5.16 and OR = 1.83, CI 95% = 1.28 to 2.63, male and female, resp.) was verified. It was concluded that violent behavior is associated with the consumption of alcoholic beverages and cigarettes among adolescents.